2011
DOI: 10.1136/postgradmedj-2011-130217
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effects of antipyretic medications on mortality in Streptococcus pneumoniae infections

Abstract: A twofold increased risk of mortality was found with aspirin treatment in animal models of S pneumoniae infection. No relevant human studies were identified. It is difficult to generalise from animal models to clinical medicine, but based on these findings and the prevalence and severity of S pneumoniae infections worldwide, future study of the effects of antipyretic therapy in S pneumoniae infection in humans is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(50 reference statements)
1
8
0
1
Order By: Relevance
“…The benefits of hyperthermia has been most convincingly demonstrated in ectoderms such as reptiles and fish, in which deliberate exposure to higher environmental temperatures improved survival [ 19 ]. Correspondingly, in rabbits, mice, and chicks, antipyretic drugs repeatedly increased mortality rates from bacterial [ 22 ] and viral [ 23 ] infections. The evidence in humans is less conclusive, as large-scale blinded trials have not been performed [ 24 , 25 ].…”
Section: The Mystery—why Do We Feel Sick?mentioning
confidence: 99%
“…The benefits of hyperthermia has been most convincingly demonstrated in ectoderms such as reptiles and fish, in which deliberate exposure to higher environmental temperatures improved survival [ 19 ]. Correspondingly, in rabbits, mice, and chicks, antipyretic drugs repeatedly increased mortality rates from bacterial [ 22 ] and viral [ 23 ] infections. The evidence in humans is less conclusive, as large-scale blinded trials have not been performed [ 24 , 25 ].…”
Section: The Mystery—why Do We Feel Sick?mentioning
confidence: 99%
“…In fact, the use of antipyretics has been reported to prolong the evolution of certain types of bacterial and viral infections [96, 97]. Studies have shown a correlation between febrile response and increased survival rate in patients with community-acquired pneumonia, Escherichia coli, Streptococcus pneumonia, and Pseudomonas aeruginosa sepsis [98101]. Fever also has the direct effect of inhibiting the replication of some microorganisms, and it enhances the antibacterial effect of a variety of antibiotics [102, 103].…”
Section: Changes In Brain Temperature In Neurointensive Carementioning
confidence: 99%
“…In this model, the elevated body temperature seen with increased ambient temperature was associated with a 100,000-fold reduction in the intraperitoneal bacterial load [19]. A recently published systematic review and meta-analysis of the effects of antipyretic medications on mortality in S. pneumoniae infection identified four animal studies comparing aspirin to placebo and demonstrated that the administration of aspirin was associated with an increased risk of death [OR 1.97 (95 %CI 1.22-3.19)] [20]. …”
Section: The Significance Of Fever In Animals With Infectionsmentioning
confidence: 99%